A hybrid knowledge-based method for pipe renewal planning in Water Distribution Systems with limited data: Application to Iran. (October 2022) - Salehi, Sattar; Robles-Velasco, Alicia; Seyedzadeh, Ali; Ghazali, Aliakbar; Davoudiseresht, Mohsen
Abstract: This study uses a hybrid knowledge-based method for pipe renewal planning in Water Distribution Systems (WDSs), which is useful when data are limited. The method is applied to eight Iranian WDSs to demonstrate its effectiveness. An evolutionary systems design negotiation method was used to identify planning criteria for pipe renewal by a 17-member team of expert planners. A group of 48 experienced system operators then ranked the criteria by a nominal group technique. The results indicate when accurate operational data are limited, it is possible to use the combined expertise of knowledgeable planners and experienced operators for planning pipe renewal. Highlights: Hybrid knowledge-based methods could be used for planning pipe renewal. Knowledge-based decisions are useful for public utilities with limited data. Knowledge of experts could be as important as field data for policymaking. Years of experience of the experts are more relevant than their degree. Knowledge-based decisions could be aligned or conflict with data-based decisions.